Wakatobi Language Variations: A Dialectological Study - Maulid Taembo (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The Wakatobi language variation is a very interesting object of study because it has very diverse variations. The study aims at describing phonological variation, the process of phonology, and the grouping of Wakatobi language. The research data was collected through interviews and analyzed using generative dialectology theory, employing intralingual equivalence and lexical dialectometry methods. The data were sourced from informants at 25 observation points (villages) in Wakatobi Regency. Based on the description of phonological variations, vowels and consonants are found to vary regularly and sporadically. Related to the tracing of derived forms from the original form, in this study, several glosses are described that are phonologically different, such as the gloss `jenggot. The realization of derived forms from the original form undergoes one or several phonological rules, such as the derived forms á¶‘aÅ‹ku and jaÅ‹gu, each derived by the rule of changing the mediopalatal stop segment /j/ to the apicoalveolar stop /á¶‘/ and changing the voiceless stop segment /Å‹k/ to the voiced stop segment /Å‹g/ from the original or underlying form jaÅ‹ku. The results of dialectometric calculations show that the Wakatobi language in Wakatobi Regency can be grouped into four large groups, which are spread across four large islands in Wakatobi. The four groups are Wangi-Wangi, Kaledupa, Tomia, and Binongko. Meanwhile, in Wangi-Wangi it can be divided again into three groups, namely Waha, Kapota, and Mandati-Lia. The geography distance or position affects the differences of the percentage distance relationship among subdialects.